Generational differences in the ranking pathways of top 100 ranked golfers - Koenigsberg, A.; Pilgrim, J.; Baker, J. (Journal of Sports Sciences, 2020)
The Official World Golf Ranking (OWGR) offers a rich data source that may be used by golf National Sporting Organisations (NSOs) to inform the allocation of human and financial capital. Golf has undergone many changes over the past few decades, thus before rankings data can be used for benchmarking purposes it is crucial to appraise its temporal stability. This study aimed to determine whether the ranking pathways of top 100 golfers have changed over time. Data were collected on 470 golfers who entered the top 100 between January 1990 and December 2018. Golfers were assigned to birth-year defined cohorts: Cohort 1 (1989-1999) (n = 79); Cohort 2 (1979-1988) (n = 153); Cohort 3 (1969-1978) (n = 174); and Cohort 4 (1959-1986) (n = 64). Descriptive statistics were reported for ranking milestones and one-way ANOVAs used to investigate temporal trends. Golfers from younger age cohorts reached milestones at significantly earlier ages and in less time than their older peers. For instance, the time taken to reach the OWGR top 100 for Cohort 1, 2, 3, and 4 was 3.55, 5.99, 7.72, and 10.23 years, respectively. Together, these findings highlight the temporal instability of golf rankings data and provide scientific data to inform athlete selection and investment decisions.